One-step synthesis of an antimicrobial framework based on covalently cross-linked chitosan/lignosulfonate (CS@LS) nanospheres. Issue 3 (28th November 2019) - Pandey, Ravi P.; Rasool, Kashif; Rasheed, P. Abdul; Gomez, Tricia; Pasha, Mujaheed; Mansour, Said A.; Lee, One-Sun; Mahmoud, Khaled A.
Abstract : Herein, renewable and uniform nanospheres based on chitosan (CS) and lignosulfonate (LS): (CS@LS) were designed for the first time through a simple one-step covalent cross-linking protocol. Abstract : Herein, renewable and uniform nanospheres based on chitosan (CS) and lignosulfonate (LS): (CS@LS) were designed for the first time through a simple one-step covalent cross-linking protocol. Experimental and theoretical pieces of evidence have proven the self-assembled structure of the nanospheres as a binary network between CS and LS. The optimum composite structure was formed at CS@LS 1 : 1 ratio, with a characteristic domain size in the range of 150–200 nm. The amphiphilic nanospheres demonstrated high thermal, mechanical, and bactericidal properties. The CS@LS-1 : 1 nanosphere demonstrated high growth inhibition towards aerobic Gram (−) E. coli and Gram (+) B. subtilis and anaerobic sulfate-reducing bacteria (SRB) making them ideal biocides for water disinfection. This work provides an important synthesis guideline for the development of green biomimetic nanomaterials for a plethora of applications, where a uniform size and shape are crucial success criteria.